Managing Knowledge at the Time of Artificial Intelligence: An Explorative Study with Knowledge Workers - Manuti, Amelia; Monachino, Dalila (Lesya Ukrainka Volyn National University, 2020)
In the evolutionary context of Industry 4.0, where machine learning and machine to machine technology are powerful tools for the maintenance and replicability of knowledge, the implementation of hybrid systems based on the use of Artificial Intelligence (AI) represents the key to organizational innovation and to the capitalization of knowledge. At the same time, the benefits of digital transformation for individuals and teams are often not so clear - and uncertainty surrounding the future often results in fear in those being impacted. Fear of changes to their job, fear of a job role change, job losses, being faced with learning new skills, new technology or new ways of working. Therefore, to secure the transition to the digitization organizations need to carefully support their human resources and to provide them with the reasons why they need to commit to change. In this perspective, the study aimed to investigate how high-qualified knowledge workers cope with this new situation. Yet, participants were a group of project managers, employed in some knowledge-based organizations, in which AI and digitalization systems are going to be introduced to improve replicability, circulation and storage of knowledge. The choice of this peculiar target of participants was guided by the acknowledgement of their important role within the organization, being project managers generally considered as agents of change. In view of the above, the main goal was to collect project managers’ expectations and fears about the upcoming integration of secularized company flows with performing process automation strategies. In-depth individual interviews were conducted and diatextual analysis was used to approach the discursive data collected. Results showed interesting insights both in terms of organizational management implications as well as of future research development. Participants showed clear awareness about the need to “go digital” to improve organizational performance and to stay competitive. However, they underlined the importance of parallel invest on human capital, improving crucial soft skills such as: openness to change, flexibility and the ability to work in a team, that could concretely support digital changes in procedures and work processes.
Keywords: knowledge management; Artificial Intelligence; knowledge workers; organizational development